2017
DOI: 10.1080/14767058.2017.1332035
|View full text |Cite|
|
Sign up to set email alerts
|

The association of placenta previa and assisted reproductive techniques: a meta-analysis

Abstract: We showed based on odds ratio reports in observational studies that ART procedures are a risk factor for placenta previa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 47 publications
2
30
2
1
Order By: Relevance
“…30,31 A 2016 meta-analysis of ART singleton pregnancies reported a RR of 3.71 (95% CI 2.67-5.16) for placenta praevia 32 that was confirmed by a 2017 metaanalysis (OR 2.67, 95% CI 2.01-3.34). 33 Furthermore, a 2017 meta-analysis of the impact of maternal smoking on placental position 34 (OR 1.42, 95% CI 1.30-1.50) has found an increased risk of placenta praevia.…”
Section: Evidence Level 2++mentioning
confidence: 99%
“…30,31 A 2016 meta-analysis of ART singleton pregnancies reported a RR of 3.71 (95% CI 2.67-5.16) for placenta praevia 32 that was confirmed by a 2017 metaanalysis (OR 2.67, 95% CI 2.01-3.34). 33 Furthermore, a 2017 meta-analysis of the impact of maternal smoking on placental position 34 (OR 1.42, 95% CI 1.30-1.50) has found an increased risk of placenta praevia.…”
Section: Evidence Level 2++mentioning
confidence: 99%
“…ARTs, and in particular IVF, have also been associated with a higher incidence of placenta praevia independently of the high rate of multiple pregnancies [14][15][16][17]. A large Swedish populationbased retrospective registry study analysis found that the risk of placenta previa is higher in pregnancies after blastocyst transfer compared to pregnancies after cleavage-stage replacements (adjusted OR (AOR), 2.08; 95% CI, 1.70-2.55) and to spontaneous conceptions (AOR, 6.38; 95% CI, 5.31-7.66) [35].…”
Section: Low-lying Placenta and Placenta Previamentioning
confidence: 99%
“…In maternal perinatal complications after ART, it has been reported to increase the risk of gestational diabetes (GDM) (OR: 1.99, 95% CI: 1.69‐2.36), gestational hypertension (OR: 2.58, 95% CI: 2.11‐3.15), preeclampsia (OR: 1.49, 95% CI: 1.12‐1.98), intrahepatic cholestasis of pregnancy (ICP) (OR: 2.86, 95% CI: 2.39‐3.42), placenta previa (OR: 2.23, 95% CI: 1.79‐2.78), placental abruption (OR: 5.06, 95% CI: 2.83‐9.06), preterm premature rupture of membranes (pPROM) (OR: 3.05, 95% CI: 2.48‐3.74), placental adherence (OR: 2.37, 95% CI: 1.90‐2.95), postpartum hemorrhage (OR: 2.72, 95% CI: 2.18‐3.41), and polyhydramnios (OR: 1.79, 95% CI: 1.26‐2.53) 27‐30 …”
Section: Risk Of Birth Defects In Children Born With Artmentioning
confidence: 99%